Hiring preferences of selected blue chips companies in Iloilo City - Bacol, Jeanette; Fajanilbo, Aileen; Macion, Catherine; Sartorio, Jeanne Lee.; Sisican, Eva Paula (2003.)
This research paper will evaluate the various hiring preferences and other qualifications of selected Blue Chips Companies in Iloilo City. Likewise, the research paper will find out the rationale behind their choices. It is composed of the background of the study, statement of the problem, objectives of the study, significance of the study, review of related literature, definition of terms, analytical framework, methodology, presentation, interpretation and analysis of data, and conclusion and recommendation of the study. The background of the study gives idea about the hiring preferences of the companies in general. This study will try to answer four related specific problems stated in the problem statement. It has four goals that will lead the researchers give recommendation. The significance of the study emphasizes the important points in applying the jobs especially to neophytes in the business world. Theories, past studies and other pertinent ideas are discussed in the review of related literature.
Research Paper (Mgt 199-Management Research). [Iloilo City : University of the Philippines in the Visayas-College of Management], March 24, 2003.